Policy mixes for biodiversity: a diffusion analysis of state-level citizens’ initiatives in Germany [dataset] - Tosun, Jale; Koch, Marcus (Universität, 2022)
The dataset contains data used to produce Figure 1 in the article.
Gesehen am 12.12.2022
Keywords: Forschungsdaten; Datenbank